Rethinking of Sustainability in the Social and Solidarity Economy from a Gender Perspective: Trajectory of a Santa Fe experience - Logiodice, Luisina María; Massera, Maricel Lorena (Cooperativismo & Desarrollo, 2017)
Purpose: This article aims to analyze the trajectory and reconfiguration of an associative experience of small agricultural producers in a semi-rural area of the province of Santa Fe in Argentina. Description: The article explores the sustainability –in a plural sense– of this type of Social and Solidarity Economy (sse) practices, as well as the participation of women in these spaces. The above makes it possible to integrate the gender dimension into an analysis of the permanence possibilities of these laboral practices. Point of view: The study’s starting point lies in current discussions about conceptions of sustainability in the sse as new forms of associative, collective and familiar work, incorporating the gender perspective as a necessary approximation in the socio-economic processes, to then analyze the case study in the light of these conceptualizations. Conclusion: It is essential to consider the connections and bonds of trust generated within the sse organizations, which allow to sustain associative pacts and group cohesion, in addition to the contribution and linkage given by the private sphere of home, which makes it possible to sustain it’s members living standards.